An unusual aetiology for internuclear ophthalmoplegia. (3rd June 2013) - Vishwas, Mellekate Shadaksharappa; Whitlow, Christopher T; Haq, Ihtsham ul
Abstract : Typical causes of internuclear ophthalmoplegia (INO) include arterial infarcts, demyelinating conditions, inflammation and trauma. We here report the unique case of a 33-year-old man with INO of the right eye caused by infarction of the right midbrain, confirmed by diffusion-weighted MRI. At presentation he displayed impaired adduction of the right eye with normal movement of the left. CT angiogram revealed an underlying developmental venous anomaly (DVA), raising the concern of venous infarction. His symptoms improved with aggressive management of blood pressure and risk factors. The patient had vascular risk factors—smoking, hypertension and dyslipidaemia—and we theorise that the hyalinised and inelastic walls of our patient's DVA were more vulnerable to the thrombogenic effects of his risk factors, predisposing him to this event. Venous infarcts owing to DVA are rare. To our knowledge INO secondary to venous infarct has not been reported, and should be considered in the differential of such cases.